2022
DOI: 10.1002/nop2.1314
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric evaluation of the acute care nurses' job satisfaction scale‐revised

Abstract: Aim:The aim of this study was to validate a job satisfaction scale among acute care nurses in the context of Qatar.Design: Cross-sectional correlational survey.Methods: A convenience sampling technique was used to recruit 295 acute care nurses between June 2021-September 2021. Exploratory factor analysis followed by confirmatory factor analysis was used for item reduction and convergent and discriminant validity evaluation. Pearson's correlations were conducted to evaluate the concurrent and convergent validit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…The Acute Care Nurses Job Satisfaction Scale‐Revised (ACNJSS‐R) assessed job satisfaction in our study (Yasin et al., 2022). The ACNJSS‐R evaluates satisfaction across five factors: supervision, workplace policy, growth and advancement, benefits, and work environment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Acute Care Nurses Job Satisfaction Scale‐Revised (ACNJSS‐R) assessed job satisfaction in our study (Yasin et al., 2022). The ACNJSS‐R evaluates satisfaction across five factors: supervision, workplace policy, growth and advancement, benefits, and work environment.…”
Section: Methodsmentioning
confidence: 99%
“…The ACNJSS‐R was validated in Qatar, showing good convergent, discernment, and criterion validity. Its composite reliability and maximal reliability were above 0.7 for all factors (Yasin et al., 2022).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the study also attained MaxR(H) as all values are above >0.70 cut point (Gaskin, James, & Lim, 2019; Sharif Nia et al. , 2019; Yasin, Kehyayan, Khraim, & Al-Lenjawi, 2022).…”
Section: Analysis and Resultsmentioning
confidence: 68%
“…Alternatively, to attain discriminant validity, the MSV for each study construct must be smaller than the AVE (Hair et al, 2022). In addition, the study also attained MaxR(H) as all values are above >0.70 cut point (Gaskin, James, & Lim, 2019;Sharif Nia et al, 2019;Yasin, Kehyayan, Khraim, & Al-Lenjawi, 2022).…”
Section: Model Fit Summary Indicesmentioning
confidence: 99%
“…22 Numerous reviews have indicated that factors such as fair remuneration, career advancement opportunities, autonomy in decision-making, positive teamwork dynamics, and a supportive work environment are crucial to developing a comprehensive job satisfaction scale for nurses. 8,[22][23][24][25][26][27][28][29] In Thailand, the existing evidence about nurses' job satisfaction scales in hospitals has revealed the presence of eight factors comprising 107 items. These factors include incentives, personal autonomy and recognition, supervisor support, social…”
Section: Introductionmentioning
confidence: 99%